'The ones that turn up are the ones that are responsible': Key stakeholders perspectives on liquor accords. (13th April 2016) - Curtis, Ashlee; Miller, Peter; Droste, Nicolas; McFarlane, Emma; Martino, Florentine; Palmer, Darren
Abstract: Introduction and Aims: Liquor accords were introduced as an intervention to reduce alcohol‐related harm in and around licensed venues. There have been very few evaluations of the accords, made all the more difficult given the multitude of measures that are often implemented under their banner. This study provides perspectives on the effectiveness of the liquor accords from key stakeholders who were involved in the strategy. Design and Methods: In‐depth interviews were conducted with 97 key stakeholders as part of a larger study, of which 46 spoke about the effectiveness of liquor accords. Responses were analysed using thematic analysis. Results: Stakeholders reported the greatest benefit of liquor accords to be their ability to improve communication. Many stakeholders recognised the need for mandatory attendance and discussed whether the accords are a waste of time of resources. Stakeholders did not generally view liquor accords as effective means of reducing alcohol‐related harm. Discussion: There was a lack of positive feedback about liquor accords provided by stakeholders, indicating a clear need to better understand the role of liquor accords, and what they aim to achieve. Responsive regulation theory suggests that the dual roles of communication and intervention are confused, leading to some of the inherent problems with accords. Conclusions: The role and aims of liquor accords need to be clearly defined. The findings suggest that separating the communication and regulatory functions from accords will lead to a clearer role for accords, and interventions and regulation might be better placed in the hands of regulators and enforcement. [Curtis A, Miller P, Droste N, McFarlane E, Martino F, Palmer D. 'The ones that turn up are the ones that are responsible': Key stakeholders perspectives on liquor accords. Drug Alcohol Rev 2016;35:273–279]